Analysis Of The Effectiveness Of The Implementation Of Government Regulation Number 62 Of 2019 On The Head Of The Batam Business Agency (BP) Ex Officio By The Mayor Of Batam In The Implementation Of Regional Government - Yunita Intan Tari; Soerya Respationo; Erniyanti Erniyanti (International Journal of Law and Society, 2024)
Batam as an industrial area which development is carried out by the Batam Island Industrial Area Development Authority agency, has also been expanded into an autonomous region which later give birth to the Batam City Government. The existence of these two government agencies then creates problems in the management of Batam City in the form of overlapping / dualism of authority. To overcome this problem, the government then issued a new breakthrough by setting the Head of the Batam Concession Agency to be held ex-officio by the Mayor of Batam in the hope that the implementation of his duties and authority would be more effective. Therefore, the purpose of this thesis research is first, the implementation of the Mayor of Batam ex Officio Head of Business Agency. Second, the ideal arrangement for the relationship between the Batam City Government and the Business Agency and third, obstacles in the implementation of ex officio. This type of research can be classified into the juridical sociological research type, because it wants to see the correlation between the law and what happens in the field so as to reveal the effectiveness of the law's application. With the research location located at the Batam Concession Agency and the Batam City Government. This research uses data sources in the form of primary data and secondary data, and data collection techniques are carried out by means of interviews, questionnaires and literature review. From the study, there are three main points that can be concluded. First, the Mayor of Batam, Muhammad Rudi, succeeded in implementing the central government's decision regarding the position of Head of the Batam Business Agency, concurrently ex-officio by the Mayor of Batam. Second, it is necessary to study Government Regulation Number 41 of 2021. and third, social problems, such as illegal houses, unemployment, crime, and others, arise as a result of inequality, public policy, inability to compete and others. As for the advice from the author; First, the need for Human Resource governance to support the duties and functions of each work unit Second, the need to re-assess/test the material of government regulation number 41 of 2021 and third, the need to develop IT innovation in the context of improving services and reporting.